Mass detection using a macro-scale piezoelectric bimorph cantilever - Rabih, A.A.S. (2013)
Piezoelectric cantilevers have found a wide usage in sensor technologies for mass sensing and energy harvesting. This paper reports theoretical calculations, Finite Element Method (FEM) simulation and experimental measurements of mass detection using piezoelectric bimorph cantilever (PZT-5H) in macro (mm) scale. The dimensions of the cantilever are 33mm, 10mm, and 0.5mm for length, width, and thickness, respectively. The cantilever has 1.325g static mass with resonance frequency of 240.036 Hz, mass sensitivity of 377 Hz/g and quality factor of 390. The calculated resonance frequency of the device was 1 and 5 higher than the measured and the simulated frequencies, respectively. Air damping is believed to be the reason for lowering values of the simulated and measured resonance frequencies. In addition the extra masses due to the material coating the piezoelectric layer of the cantilever also play a role. Attachment of 8.96mg mass on the tip of the cantilever found to induce â¼4 Hz frequency shift. Due to the reasonable mass sensitivity of the cantilever, it could be used for mass sensing applications. Â© 2013 IEEE.